The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1516-35982008000200019
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação nutricional da grama-estrela cv. Africana para vacas leiteiras em condições de pastejo

Abstract: RESUMO -Objetivou-se avaliar nutricionalmente a grama-estrela ( Cynodon nlemfuensis) cv. Africana utilizada sob pastejo rotacionado por vacas leiteiras. Dez vacas mestiças foram manejadas em 2 ha de grama-estrela e divididas em 11 piquetes/ha. O período de pastejo foi de três dias e os 30 subseqüentes foram destinados à recuperação da pastagem. Durante o período experimental, os animais foram ordenhados duas vezes ao dia e receberam suplementação com 2 kg de concentrado. Amostras representativas do pasto inger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
12
0
3
Order By: Relevance
“…The use of the CNCPS model to evaluate diets is useful to estimate the nutritive value of different forage resources and other tropical foragebased diets (Cabral et al, 2000;Vieira et al, 2000a,b,c). The dietary synchronization is important for microbial growth and, depending on the availability of non-fibrous carbohydrates, the microbial biomass uses degradable nitrogen more efficiently Malafaia et al, 1998;1999;Vieira et al, 2000c;Favoreto et al, 2008;Fernandes et al, 2014). Because of the nutritional imbalances of sugarcane, e.g., high soluble sugars and low protein content, it should be used with caution to prevent excess nutrient losses (Fernandes et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The use of the CNCPS model to evaluate diets is useful to estimate the nutritive value of different forage resources and other tropical foragebased diets (Cabral et al, 2000;Vieira et al, 2000a,b,c). The dietary synchronization is important for microbial growth and, depending on the availability of non-fibrous carbohydrates, the microbial biomass uses degradable nitrogen more efficiently Malafaia et al, 1998;1999;Vieira et al, 2000c;Favoreto et al, 2008;Fernandes et al, 2014). Because of the nutritional imbalances of sugarcane, e.g., high soluble sugars and low protein content, it should be used with caution to prevent excess nutrient losses (Fernandes et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Favoreto et al (2008) observed levels of 20.37 g/100 g in star grass (Cynodon nlemfuensis). Vieira et al (2000) highlighted the importance of determining this fraction, as it is considered to be unavailable in the rumen and the intestines.…”
Section: Resultsmentioning
confidence: 92%
“…Fractions A' (simple sugars) and B 1 ' (non-fibrous complex carbohydrates) were estimated by in vitro gravimetric and gas production techniques. A gravimetric profile of degradation of neutral detergent fiber corrected for ash and protein (NDFap) was obtained after incubation of samples (Favoreto et al, 2008).…”
Section: Revista Brasileira De Zootecniamentioning
confidence: 99%
See 2 more Smart Citations